Velocity Distribution at Contraction Zone Around Bank–Protection Structures - Shehab, Abdul Kareem S. (Al-Mukhtar Journal of Sciences, 1999)
In this study, some observations at the zones of streamflow around bank– protection structures were discussed, and their characteristics were fixed, and were divided into three zones: afflux, contraction and expansion. The contraction zone was also, divided into subzones according to their deformation and distortion due to the disturbance which happens from the structure. It was found analytically that, in two zones the velocity distribution pattern similar to that, which was given in the theory of turbulence of Schlichting–Abramovich. Also the backward–velocity distribution profiles were studied with their characteristics and formation. A formula for calculating backward–velocity distribution was derived at the zone of contraction using integral relationship of the discharge at the section in the velocity distribution profile which, was obtained from the results of author’s experiments. This study can be useful to calculate the lengths and velocities of the different flow zones, also during river diversion works, for calculating permissible velocities, protection of banks against scouring or erosion and for river training works.